The influence of talent management and employee performance of public health center pagar jati deliserdang in north sumatera province - Naibaho, Togar; Sari Sirait, Syah Paradiba; Naibaho, Winfrontstein (Jurnal Mantik, 2024)
This research aims to determine the influence of talent management, performance allowances and self-awareness on the performance of employees of the UPT. Puskesmas Pagar Jati Deliserdang Regency through employee well-being. The type of research used is quantitative descriptive. The research population is employees who work at the UPT. Puskesmas Pagar Jati Deliserdang Regency with a sample size of 114 employees. The data analysis technique uses structural equation modeling (SEM) with the Smart PLS analysis tool version 4.0. The research results show that: (1) talent management has a positive but not significant effect on employee well-being, (2) talent management has a positive and significant effect on employee performance, (3) performance allowances have a positive and significant effect on employee well-being, (4) performance allowances have a positive and significant effect on employee performance, (5) self-awareness (self awareness) has a positive and significant effect on employee well-being, (6) self-awareness has a positive and significant effect on performance, (7) employee well-being (employee well-being) has a positive and significant effect on employee performance. (8) talent management has a positive and insignificant effect on employee performance through employee well-being as an intervening variable, (9) performance allowances have a positive and significant effect on employee performance through employee well-being as an intervening variable , (10) self-awareness has a positive and significant effect on employee performance through employee well-being as an intervening variable